2009
DOI: 10.1111/j.1471-0528.2009.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of obstetric services for very preterm births in Europe: results from the MOSAIC project

Abstract: Objective To study the impact of the organisation of obstetric services on the regionalisation of care for very preterm births.Design Cohort study.Setting Ten European regions covering 490 000 live births.Population All children born in 2003 between 24 and 31 weeks of gestation.Method The rate of specialised maternity units per 10 000 total births, the proportion of total births in specialised units and the proportion of very preterm births by referral status in specialised units were compared.Main outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Outcomes for extremely premature infants are improved for those infants born in hospitals with high-volume specialist neonatal care units. 19 Blondel et al 62 reported that in 2003, across a range of European regions, 2-28% of birth units were associated with a 'large neonatal unit' (≥ 50 admissions per year for infants with a gestational age of < 32 weeks). Between 8% and 61% of all births were in hospitals with large neonatal units, but 37-76% of births of infants with a gestational age of < 32 weeks were achieved in such units (20-54% of births of infants with a gestational age of < 32 weeks were achieved in such units without requiring in utero transfer).…”
Section: The Interface Between Obstetric and Neonatal Carementioning
confidence: 99%
See 2 more Smart Citations
“…Outcomes for extremely premature infants are improved for those infants born in hospitals with high-volume specialist neonatal care units. 19 Blondel et al 62 reported that in 2003, across a range of European regions, 2-28% of birth units were associated with a 'large neonatal unit' (≥ 50 admissions per year for infants with a gestational age of < 32 weeks). Between 8% and 61% of all births were in hospitals with large neonatal units, but 37-76% of births of infants with a gestational age of < 32 weeks were achieved in such units (20-54% of births of infants with a gestational age of < 32 weeks were achieved in such units without requiring in utero transfer).…”
Section: The Interface Between Obstetric and Neonatal Carementioning
confidence: 99%
“…There are three general models for trying to achieve births of preterm infants in units with large neonatal units (and these models may be mixed): (1) consolidation of births into higher-volume units that may sustain a large neonatal unit, (2) identifying mothers at a high risk of preterm delivery and booking those mothers to deliver in high-volume neonatal units and (3) in utero transfer during labour. Blondel et al 62 noted that different European regions were achieving reasonable rates of birth of premature infants in units with large neonatal units by using different organisational models; however, there was still a significant proportion of births (24-63%) of premature infants not occurring in units with large neonatal units.…”
Section: The Interface Between Obstetric and Neonatal Carementioning
confidence: 99%
See 1 more Smart Citation
“…Ключовою проблемою зменшення перинатальних втрат є створення можливостей для виходжування дітей з дуже малою масою тіла при народженні, адже саме з ними пов'язана приблизно половина всіх випадків перинатальних втрат. того, діти, що народилися з дуже малою масою тіла, складають групу ризику щодо розвитку захворювань, що формують показники інвалідності [11,13,15].…”
unclassified
“…За даними ВООЗ у економічно розвинених країнах виживання новонароджених у перші 168 годин життя з масою тіла при народженні 500 -999 г складає 30,0%, а новонароджених з масою тіла при народженні 1000 -1499 г -70,0% [4,12,13]. Виживання дітей з дуже малою масою тіла при народженні в США, Японії і більшості країн Західної Європи досягло 80 і 95% відповідно [7,11,15].…”
unclassified